HOMOSEKS DAN LESBIAN PERSPEKTIF HUKUM ISLAM - Fatmawati Fatmawati (DIKTUM: Jurnal Syariah dan Hukum, 2015)
Gay and lesbian issued in this paper analyzed from two perspectives, namely the views of Islamic law against sexual perversion in the form of gay and lesbian, and the sanctions given for gay and lesbian. By using a normative approach, it was concluded that the scholars agreed that homosexual and lesbian acts are haram/ prohibited. However, scholars are still different opinions in determining punishment for the perpetrators. Some scholars argue that the perpetrators should be killed or stoned both muhsan and ghairu muhsan. Some scholars assign ta’zir penalty on the grounds that this action is only one form of immorality. That is not specified shape and just love on the penalty spot unwanted by normal instincts. Because of that, perpetrators don’t not gain had punishment.